Nonformal education a handbook for teacher education students, NFE administrators and extension program implementors - Cabag, Ramon C. (Quezon City Katha Pub., 1999)
This book has four parts. Part one introduces the nonformal program, its nature, scope, characteristics and principles. Part two discusses the "education for all" Philippine plan of action. Part three presents the characteristics of the nonformal education learners and teachers and principles of adult teaching, as well as contemporary approaches or methods and other strategies. Part four provides reason why the nonformal education program should be evaluated.
Contents: Nature, scope, characteristics and principles of nonformal education. "Education for All" Philippine Plan of Action. NFE learners and adult teaching and learning. Reasons of evaluation of nonformal education.
Purpose: "To provide pre-service education students with the basic knowledge about the nonformal education program."
Keywords: Non-formal education -- Philippines -- Handbooks, manuals, etc; Vocational education -- Philippines -- Handbooks, manuals, etc